DESIGN OF FORCE MEASURING SYSTEM ON MAIN LANDING GEAR WEIGHT DROP TESTING MACHINE FOR THE APPLICATION OF LSU SERIES - Wijaya, Yusuf Giri; Nurrohmad , Abian (BRIN Publishing, 2020)
In this research, the design of the force measuring system on main landing gear weight drop test for the LSU series that developed by LAPAN was carried out. The principle of this machine is to apply the load according to the weight of the aircraft on the main landing gear and drop it at a certain height assisted by the guiding rail. At the bottom of this machine there is a impact platform where each angle is mounted with a load cell that functions to measure the reaction force due to the impact of the main landing gear. In addition, there is a data acquisition system whose function is to process the output signal from load cell and display measurement data. The data acquisition system used consists of DAQ measurement hardware made by national instruments and LabVIEW software installed on a PC. The design of this testing tools aims to carry out a dynamic impact test on the main landing gear structure of the UAV. In this study, static calibration has also been successfully performed on the impact platform and shows consistent results for various test masses.